Hepatic Gene Expression Profiles Are Altered by Dietary Unsalted Korean Fermented Soybean (Chongkukjang) Consumption in Mice with Diet-Induced Obesity - JuRyoun Soh; Dae Young Kwon; Youn-Soo Cha (Journal of Nutrition and Metabolism)
We found that Chongkukjang, traditional unsalted fermented soybean, has an antiobesity effect in mice with diet-induced obesity and examined the changes in hepatic transcriptional profiles using cDNA microarray. High-fat diet-induced obese C57BL/6J mice were divided into three groups: normal-diet control group (NDcon, 10% of total energy from fat), high-fat diet control group (HDcon, 45% of total energy from fat), and HDcon plus 40% Chongkukjang (HDC) and were fed for 9 weeks. The HDC group mice were pair-fed (isocalorie) with mice in the HDcon group. Final body weight, epididymal fat accumulation, serum total cholesterol, and LDL-cholesterol were improved in HDC group. The cDNA microarray analyses revealed marked alterations in the expression of about 800 genes. Several genes involved in fatty acid catabolism (Acaa2, Mgll, Phyh, Slc27a2, and Slc27a5) were normalized by Chongkukjang consumption. This study showed beneficial effects of Chongkukjang consumption in preventing diet-induced obesity and related metabolic abnormalities.